Proposed wax refinery - Angeles, Anita (College of Engineering, 1963)
This project involves thd esign of a wax refinery using propane as solvent. The following results were obtained : for a capacity of 4,000,000 pounds of paraffin wax which is 1/3 the present demand based on importations for 1961.